PERBANDINGAN EFEKTIVITAS ANTARA IBUPROFEN DAN ASAM MEFENAMAT TERHADAP TINGKAT DISMENORE PADA MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS BATAM - Hendra, Putra; Tjendera, Mariman; Dwitanto, Rico Febrian (Universitas Batam, 2024)
Background: Dysmenorrhea is abdominal pain caused by uterine cramps that occur during menstruation. The pain is caused by the start of menstruation and lasts several hours to several days until it reaches peak pain. Dysmenorrhea treatment is divided into 2, namely pharmacology therapy and non-pharmacology therapy. Pharmacological treatment, namely non-steroidal drug therapy, is believed to be an anti-inflammatory or analgesic (NSAID), for example: ibuprofen and mefenamic acid are often used to treat dysmenorrhea. Methods: This research uses a quantitative design one group pretest – posttest method with a quasi-experimental approach. This research was conducted at Batam University in November 2023. The sampling technique is simple random sampling with a sample size of 32 or 16 respondents per group. Results: The results of the Paired T Test showed the effect of mefenamic acid 500 mg and ibuprofen 200 mg intervention on the level of dysmenorrhea. The p-value was 0.001, which was smaller than the p-value of 0.05, meaning there was a difference in reducing the level of dysmenorrhoea pain in the mefenamic acid 500 mg and Ibuprofen 200 mg intervention. The average difference in dysmenorrhoea pain during intervention was 0.687. This shows that Ibuprofen 200 mg is able to reduce 0.687 times greater than administering mefenamic acid 500 mg. Conclusion: Based on the research results, the results show that there is a comparison of the effectiveness between mefenamic acid and ibuprofen on the level of dysmenorrhea in female students at the Faculty of Medicine, Batam University.